Characteristics of phytoplankton communities and their biomass variation in a gas hydrate drilling area in the northern South China Sea. (August 2018) - Wang, Yu; Kang, Jian-hua; Liang, Qian-yong; He, Xue-bao; Wang, Jian-jun; Lin, Mao
Abstract: We analyzed the data obtained from field observations on a gas hydrate drilling area in Dongsha of northern South China Sea (SCS) in middle May (before drilling) and early October (after drilling) in 2013. The variation in the phytoplankton communities and biomass as well as the impacts of environmental factors including dissolved methane was studied. Results indicated that the gas hydrate drilling area in Dongsha, SCS exhibited a typical low-nutrients low-chlorophyll a (LNLC) environment accompanied with low phytoplankton abundance. A total of 103 taxa belonging to 52 genera of 5 classes were identified, with diatoms and dinoflagellates dominating the community. Both phytoplankton abundance and chlorophyll a (Chl a ) were highest at the subsurface maximum layer. The subsurface chlorophyll maximum (SCM) before and after drilling were stabilized at 75 m (0.30 ± 0.06 mg/m 3 and 0.51 ± 0.29 mg/m 3, respectively), while the subsurface maximum of abundance after drilling went deeper to 75 m (604.17 ± 313.22 cells/L) from the surface (707.14 ± 243.98 cells/L) before drilling. After drilling, phosphate and Chl a increased significantly, but no significant differences were observed on abundance. Dominant species of diatoms were basically constant with dinoflagellates becoming more apparent in higher occurrence and abundance, while Cyanophyta was diverse after drilling. Redundancy analysis (RDA) and Spearman's correlation analysis both indicated that temperature, pH and phosphates were major factors causing fluctuation in phytoplankton community structure, while dissolved methane had non-significant impact directly. We clearly found both abundance and Chl a increased in particular water layers (between 50 and 75 m) and at stations (DS06, DS08 and DS15) where dissolved methane concentrations were also abnormally high. This study appeared to partly coincide with the findings of natural oil seeps in the Gulf of Mexico, which assumed that the turbulence from the natural oil and gas leaking zone could raise the bottom water through the rising bubbles and bring cold nutrient rich waters to the thermocline from the deep seeps. This plume-generated upwelling could then fuel a bottom-up effect on the photosynthetic species in the upper pelagic waters within the euphotic zone. Highlights: The gas hydrate drilling area in Dongsha, SCS exhibited a typical low-nutrients low-chlorophyll a environment accompanied with low phytoplankton abundance. After drilling, phosphate and Chl a increased significantly, but no significant difference in abundance. Temperature, pH and phosphates were major factors causing phytoplankton fluctuation, while dissolved methane had non-significant impact directly. Abundance and Chl a increased in particular water layers and at stations where dissolved methane concentrations were abnormally high. We emphasized decrease in pH of ocean acidification was closely related to seabed gas hydrates decomposing.